The "greening" of industrial policy, headwinds and a possible symbiosis - Karl Aiginger (WWWforEurope, 2013)
The importance of manufacturing for industrialized countries has been reappraised, specifically in the wake of the financial crisis and of China's rise to world no 1 in manufacturing. A "new industrial policy" should bolster reindustrialization, different from the old selective and interventionist one, with proposals by academia, by the European Commission and many national policy makers in the US, United Kingdom and France. It should be pro competitive, in line with societal needs, integrated with innovation and regional policy building on competitive strength and with "sustainability at centre stage". Environmental standards should no longer be considered as an obstacle to competitive manufacturing but could constitute a driver of green growth. Europe sets targets for increasing energy efficiency, increasing shares of renewable and cutting emission first for 2020 and then for 2050, demanding the reduction of greenhouse gases by 80%-90%, based on new technologies and prices of carbon dioxide of 250 exteuro/t. Headwinds to this ambitious path come from low gas prices specifically in the US, based on a new extraction technology and from the breaking down of the European emission trading. The question now raises whether Europe has to cope with low gas prices as to prevent carbon leakage, or whether Europe can stick to the goals of the envisaged integrated and systemic industrial policy as to raise energy efficiency as well as to reduce carbon emissions by new technologies. A "new industrial policy" would match the US cost advantage in energy by closing the technology deficit, improving skills and going for excellence in energy efficiency and clean technologies.
Keywords: L5; O32; O44; Q3; Q4; Q5; 330; new industrial policy; climate change; carbon leakage